2020
DOI: 10.3389/fcell.2020.572749
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 Alters Tight Junction Proteins Expression Thereby Compromising Barrier Function and Dampens Rhinovirus Induced Immune Responses in Nasal Epithelium

Abstract: Tight junctions (TJs) are intercellular structures which are essential for epithelial barrier function and play an important role in antimicrobial defense. Epithelium dysfunction and type-2-skewed inflammation are two main pathological phenomena of chronic rhinosinusitis with nasal polyps (CRSwNP). However, the effect of pro-inflammatory type-2 cytokine IL-13 on TJs in CRSwNP is poorly understood. Nasal biopsies of CRSwNP patients and in vitro IL-13-matured human nasal epithelial cells (hNECs) were used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 36 publications
6
43
0
Order By: Relevance
“…IL-13 increases mucus secretion, goblet cell hyperplasia and AHR, which are typically detrimental, although some investigators have reported beneficial effects in parasitic infections ( 48 , 49 ). In influenza infection, IL-13 can compromise the epithelial barrier ( 50 , 51 ) and predispose to a more severe form of disease ( 52 ), as also seen in our study. Furthermore, continuous production of IL-13 by macrophages following lung inflammation can result in chronic lung disease ( 53 ).…”
Section: Discussionsupporting
confidence: 83%
“…IL-13 increases mucus secretion, goblet cell hyperplasia and AHR, which are typically detrimental, although some investigators have reported beneficial effects in parasitic infections ( 48 , 49 ). In influenza infection, IL-13 can compromise the epithelial barrier ( 50 , 51 ) and predispose to a more severe form of disease ( 52 ), as also seen in our study. Furthermore, continuous production of IL-13 by macrophages following lung inflammation can result in chronic lung disease ( 53 ).…”
Section: Discussionsupporting
confidence: 83%
“…In terms of IL-13, overexpression of miR-143 in IL-13-stimulated nasal epithelial cells (NECs) from AR patients suppressed the production of IL-13-induced inflammatory cytokines, and miR-143 rendered these effects by directly targeting and repressing IL13RA1 transcript expression ( Teng et al, 2015 ). Treatment of human NECs with the cytokine suppressed the expression of TJ molecules including ZO-1 and CLDN3 ( Huang et al, 2020 ). Moreover, correlation analysis of our cohort of AR and non-allergic control groups showed that serum IL-4 and IL-13 levels were positively associated with IL13RA1 expresion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intestinal epithelial barrier is the first barrier for preventing bacteria, antigens, and other toxic and harmful substances from entering the submucosa of the intestine and blood ( Han et al, 2015 ). The TJ structure is composed of TJ proteins, such as ZO-1, occludin, and claudins, which are an important part of the intestinal epithelial barrier and play important roles in intestinal epithelial cells ( Huang et al, 2020 ). Lin et al (2019) investigated the effect of the antimicrobial peptide gloverin A2 (BMGlvA2) on ETEC-induced intestinal barrier disruption in mice and found that it clearly improved the expression of the TJ protein ZO-1 in the intestine after ETEC infection.…”
Section: Discussionmentioning
confidence: 99%